2021
DOI: 10.1002/jsfa.11713
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for soybean yield forecasting in the Brazilian Cerrado

Abstract: BACKGROUND: We evaluated different machine learning (ML) models for predicting soybean productivity up to 1 month in advance for the Matopiba agricultural frontier (States of Maranhão, Tocantins, Piauí, and Bahia). We collected meteorological data on the NASA-POWER platform and soybean yield on the SIDRA/IBGE base between 2008 and 2017. The ML models evaluated were random forest (RF), artificial neural networks, radial base support vector machines (SVM_RBF), linear model and polynomial regression. To assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This study showed that machine learning models using monthly climate averages were more accurate than linear regression to predict soybean yield, which consolidates evidence from numerous studies [9,22,23,27] in this area of research. In addition, RF models were less sensitive to the method chosen to aggregate climate data compared to LR models, whose performances strongly varied among the tested approaches.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study showed that machine learning models using monthly climate averages were more accurate than linear regression to predict soybean yield, which consolidates evidence from numerous studies [9,22,23,27] in this area of research. In addition, RF models were less sensitive to the method chosen to aggregate climate data compared to LR models, whose performances strongly varied among the tested approaches.…”
Section: Discussionsupporting
confidence: 85%
“…Among ML techniques, RF was found to be one of the best algorithm in soybean yield prediction [9,22,23] as well as in other major crops including wheat [51] or maize [11]. Other articles report that other algorithms which have not been considered in our study such as neural networks [27] also perform well to forecast yield of soybean.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Thanks to their greater flexibility, machine learning algorithms such as RF [29], (extreme) gradient boosting [37,38], and deep learning [39] are widely employed to predict yields of crops from climatic predictors [36,40] and often outperform traditional methods such as LR or process-based models, particularly in soybean yields predictions [8,41,42]. Among these techniques, RF was found to be one of the best algorithm in soybean yield prediction [8,41,42] as well as in other major crops including wheat [43] or maize [44]. Previous articles report that other algorithms which have not been considered in our study such as neural networks [12] also perform well to forecast yield of soybean.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this resource can be used to correct outliers and fill data gaps. Several works in the literature have explored using gridded datasets for crop yield prediction [28,[40][41][42]. However, only a few studies, such as Bai et al [38]; Bender and Sentelhas [43]; Battisti et al [44] and Duarte and Sentelhas [11], aimed to compare in situ and gridded data, which is essential for helping the modeler or decision-maker to choose which data sources to use on his/her crop yield prediction model.…”
Section: In Situ and Gridded Data For Crop Yield Predictionmentioning
confidence: 99%